2004
DOI: 10.1007/s00264-004-0579-5
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric allograft microbiology

Abstract: This study aims to determine the contamination rate of cadaveric bone allograft and blood cultures retrieved from 119 donors within Leicester between 1990 and2003. A contamination rate of 27% was present, with 120 of 437 bone allografts culturing positive at the time of retrieval. Similarly, a contamination rate of 37% was present, with 40 of 107 blood samples culturing positive. The time interval between death and procurement did not influence blood contamination. Coagulase-negative Staphylococcus was the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 12 publications
(16 reference statements)
4
18
0
Order By: Relevance
“…These rates parallel those in other studies that evaluated contamination rates in living and cadaveric donor musculoskeletal allografts Martinez et al 2003;Vehmeyer et al 1999Vehmeyer et al , 2002. The incidence of Clostridium species contamination of tissue allografts obtained from cadaveric sources has ranged from 1% to 8% Ibrahim et al 2004;Martinez et al 2003), although the clinical significance of this rate is uncertain. Spore-forming organisms such as Clostridium species clearly require special consideration during procurement and processing of allograft tissues.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These rates parallel those in other studies that evaluated contamination rates in living and cadaveric donor musculoskeletal allografts Martinez et al 2003;Vehmeyer et al 1999Vehmeyer et al , 2002. The incidence of Clostridium species contamination of tissue allografts obtained from cadaveric sources has ranged from 1% to 8% Ibrahim et al 2004;Martinez et al 2003), although the clinical significance of this rate is uncertain. Spore-forming organisms such as Clostridium species clearly require special consideration during procurement and processing of allograft tissues.…”
Section: Discussionsupporting
confidence: 61%
“…On the basis of their evaluation, the CDC recommended that physicians consider Clostridium species as a potential cause of infections after allograft use and that antimicrobial treatment should be tailored accordingly. Subsequent studies have shown that contamination with Clostridium species is not unusual in allografts harvested from cadaver donors Ibrahim et al 2004). Further evaluation by Kainer et al (2004) in 2004 showed deficiencies in processing and preparation techniques by a single tissue bank that likely resulted in suspect implantations.…”
Section: Introductionmentioning
confidence: 97%
“…Concerns, however, exist regarding the efficacy of frozen or freeze dried allograft, the potential of immunogenicity, and the hazard of microbial contamination, though the rate of disease transmission has proven to be low [1,13,24,26,47]. In addition, the use of allograft is associated with considerable expense, and patients' reservations towards allograft implantation may play an important role as well [23].…”
Section: Introductionmentioning
confidence: 99%
“…In most research in which there are both bone and hemoculture samples, the highest bacteria contamination levels are found in the latter (Deijkers et al 1997;Ibrahim et al 2004;Vehmeyer et al 2002). Vehmeyer's findings showed that there was a greater risk of contamination in blood brought about by highly virulent microorganisms such as Staphylococcus spp., Streptococcus spp., and Escherichia coli in those cases in which the donor had died violently (Vehmeyer et al 2002).…”
Section: Discussionmentioning
confidence: 97%